Asesmen dalam Kurikulum Merdeka Perspektif Pendidikan Agama Islam - Hasmawati Hasmawati; Ahmad Muktamar (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This research aims to examine the implementation of assessment in the Independent Curriculum from an Islamic Religious Education perspective. This research uses a descriptive qualitative approach. Data collection was carried out through library research methods. This research focuses on examining various types of literature such as books, notes, and previous research reports which reveal the implications of the independent learning policy for the development of assessments in the Independent Curriculum from the perspective of Islamic Religious Education. The main source of information in this study is the Freedom to Learn curriculum policy issued by the Ministry of Education and Culture of the Republic of Indonesia. In addition, the secondary sources used include national and international journal articles, state laws, and other relevant sources to dig up information regarding the assessment development model in the Independent Curriculum from the perspective of Islamic Religious Education. The research results show that assessment in the Independent Learning Curriculum has an important role in ensuring the smooth learning process. This is done by the teacher or educator to identify the talents and interests of students, so that the teacher can prepare appropriate teaching. Assessment includes two types, namely cognitive diagnostic assessment and non-cognitive diagnostic assessment. In addition, there are two stages of assessment, namely formative assessment at the beginning and during the learning process, and summative assessment at the end of learning or semester. Islamic religious education and the independent learning approach have a close relationship. Research shows a significant link between the two, strengthening the relevance of Islamic education in the context of free learning.